A RESEARCH ON HUMANISM IN THE ZOROASTRIAN GATHAS - Hashimi, Sayed Asghar; Ghani, Sayed Ghani; Rahmani, Shafiqullah (American International Journal of Social Science Research, 2021)
In this article, human thoughts and the idea of human sympathy with human in Zoroaster’s Gathas have been presented which forms a fundamental part of the theory of humanism. Quotes of Zoroaster have been taken from the Gathas and after analysis; their humanistic thinking has been clarified. The research has introduction to Gathas, what humanism is, and also contains information about Zoroaster. The material has been taken from books and has been clearly explained and elaborated. The purpose of the article is to shed light on human originality in Zoroastrian quotes. This is a library research and its method is explanatory and descriptive. The findings of this article is that in the Gathas (collection of quotes) of Zoroaster, human thoughts and guidelines, like other religions, are evident and he has been manifested as a good human being. The value of this writing lies in the fact that human guidance has been offered to human beings and Zoroaster provides ideas as a humanist and his human advice form the basis and foundation for the human beings of the society.